Association of High-Sensitivity C-Reactive Protein and Vitamin D with Bronchial Asthma - Al-Athari, Ali Jihad Hemid; Aldhalmi, Ahmed Khalid; Al-Hindy, Hayder Abdul-Amir Makki (Open Access Macedonian Journal of Medical Sciences, 2022)
Background: Bronchial asthma (BA) is a common lung illness and a significant health concern affecting over 315 million individuals globally. Asthma involves three main pathologies: airways hyperresponsiveness (AHR), inflammation, and remodeling. VitD has a forceful immunomodulatory effect able of reducing inflammatory responses in many cells intricate in BA. Deficiency of vitD has been linked with much inflammation and global worsening of asthmatic patients. C-reactive protein (CRP) is elevated in primary stages of inflammation of BA and high serum CRP values are observed with impaired pulmonary function and AHR. For that reason, it is sensible to explore the role of vitD in BA via its associations with CRP. This comparative study was aimed to evaluate the relationship between serum levels of HSCRP and vitD in patients with asthma. Patients and Methods: This is a case-control study conducted on 127 asthmatic patients with 113 (sex/aged matching) healthy control. The FeNo results had obtained in private centers, according to the ''guidelines of the American Thoracic Society (ATS)''. All participants had blood analysis of HSCRP and correlated with FeNo measures. VitD Values were classified as sufficient (>30ng/ml), insufficient (20 to 30ng/ml), and deficient (<20ng/mL) based on the preceding reference. Statistical Package for Social Sciences (SPSS/23-IBM) had used. The chi-squared test had used for univariate investigation, and a t-test had completed detecting variations between the studied groups, treatment groups, and genders. The outcomes had calculated at a 95% CI and had assigned as significant for all variables. The categorization accuracy of HSCRP, vitD, and FeNo measures had been investigated under the ''ROC curves'' for their diagnostic fitness to decide asthma prediction. Results Compared to the control group, the mean FeNo levels were significantly higher in asthmatics (p-0.001). Vitamin D mean levels were parallel between the study groups (p>0.05). The mean HSCRP levels were significantly (p-0.03) higher among asthmatics. Around 40% of all participants had lower than normal levels of serum VitD and <10% only revealed deficient levels. There was no effect of history of the treatment of BA on the blood levels of vitD and HSCRP. There was a positive non-significant correlation of vitD with FeNo results (r-0.067, p-0.54) and negative non-significant (r-0.082, p-0.086) correlation of vitD with HSCRP. ROC-curve analysis showed a significant ability (p-0.001) of FeNo to distinguish asthma, with high accuracy, sensitivity and specificity: 0.967, 93.5%, 93.2%, at 95% CI [0.946-1.000], respectively. Likewise, ROC analysis of HSCRP revealed significant ability (p-0.001), but with lower accuracy (0.881), sensitivity (87.1%), and specificity (76.3%) at 95% CI [0.812-0.950] to distinguish asthma patients from healthy subjects. Unlikely, VitD had a non-significant (p-0.085) and lower ability to predict asthma from healthy participants showing AUC (0.612), sensitivity (54.8%), and specificity (68.3%) at 95% CI [0.488 -0.736]. Conclusion No relation or minor conflicting correlations between serum levels of vitD with asthma severity, treatment history, and inflammation (as indicated by HSCRP). Highly sensitive CRP is correlated with asthma.